L'università che vorremmo Proposte e riflessioni di studenti ed ex studenti - Lugaresi, Nicola (Interventi, 2021)
This book brings together forty-five contributions from students and former students of the Faculty of Law at the University of Trento, who have been given a single "lighthouse", the title: "The university we would like". In a personal way, each of them tackled a theme that was close to their hearts. The contents were then organised into six sections: "University and values"; "Community"; "University and growth"; "Students"; "University and transitions"; "Relations". Reading it can provide a snapshot of the existing university and the university that could exist, seen through the eyes of those who live it or have lived it, showing both confirmed and betrayed expectations and identifying the most "felt" problems. Reading it, on the other hand, can also show how the university must recover spontaneity and curiosity, freely consulting the people who attend it. There are things to say, there are people who are willing and able to say them. The book is aimed at students, lecturers, members of decision-making bodies at different levels, and anyone with an interest in university issues and the opinions of students and former students. But it is also aimed at those high school students who are curious to know more about the university and its dynamics, seen from personal perspectives based on experience.